Alpha-1 antitrypsin promotes re-epithelialization by regulating inflammation and migration - Farber, Idan; Wated, Muhammad; Schuster, Ronen; Sheffer, Lihie; Anav, Yuval; Ogen-Shtern, Navit; Tsitrina, Alexandra; Tacruri, Diya; Bunin, Anna; Nagar, Noah Benjamin; Hagbi Bal, Maayan; Eliyahu, Tomer; et al. (Frontiers in Immunology, 2025)
PurposeRegulation of inflammation and re-epithelialization are critical for efficient wound healing. This study explores the role of human α1-antitrypsin (hAAT), an immunomodulatory protein, in modulating inflammation and promoting re-epithelialization across various epithelial cell types.MethodsIn-vitro, epithelial gap closure and migration assays were performed using two human epithelial cell lines—HaCaT and A549 cells with and without mitomycin C treatment. These cell lines were also used in an in-vitro gel-directed epithelial migration assay. Cells were treated with hAAT, and the gap area was measured using image analysis. Gene expression of inflammatory markers (IL-1β, IL-6, and TNFα) and adhesion molecules (desmoglein-1, plectin, and integrin α6β4) were analyzed using qPCR. In-vivo, corneal abrasions were induced in C57BL/6 mice using an Ophthalmic Burr. Mice received topical hAAT treatment immediately after injury and every 6 hours thereafter. Wound closure was assessed by applying the standard ophthalmic staining technique, fluorescein, and image analysis. Inflammatory markers and adhesion molecule expression were evaluated using qPCR and immunohistochemistry.ResultsIn-vitro, hAAT accelerated epithelial gap closure and increased migration distance, independent of cell proliferation. hAAT-treated cells also exhibited earlier peak expressions of IL-1β and IL-6. In-vivo, hAAT treatment accelerated corneal wound closure and resulted in a preference for IL-1Ra over IL-1β expression. hAAT also enhanced the expression of desmoglein-1, plectin, and integrin α6β4, both in-vitro and in-vivo, and increased desmoglein-1 expression in the epithelial migration zone of mouse cornea.ConclusionshAAT enhances re-epithelialization by modulating inflammation, promoting epithelial cell migration, and regulating expression of adhesion molecules.